Pengaruh Kualitas Pelayanan, Partisipasi Anggota dan Motivasi Berkoperasi Terhadap Sisa Hasil Usaha : (Studi Kasus pada Koperasi KSP Kopdit Pintu Air Cabang Lekebai) - Lorensius Jufrianus Siso; Pipiet Niken; Wihelmina Maryetha Yulia (Universitas 45 Surabaya, 2024)
This research aimed to examine the impact of member participation, service quality, and cooperative motivation on the business performance of KSP Kopdit Pintu Air Lekebai Branch. The research gathered primary data through the distribution of questionnaires to 97 members of the KSP Kopdit Pintu Air of Lekebai Branch. The data was analyzed using multiple linear regression analysis. Hypothesis testing was conducted using the F-test and t-test. Based on the descriptive analysis, the service quality variable falls into the